Hot Spots of Integrase Genotypic Changes Leading to HIV-2 Resistance to Raltegravir - Charpentier, Charlotte (American Society for Microbiology (ASM), 2011)
We studied seven heavily pretreated HIV-2-infected patients exhibiting a virological failure while receiving a salvage raltegravir-containing regimen. At the time of virological failure, different resistance genetic pathways were observed: T97A-Y143C, Q148K, Q148R, G140S-Q148R, E92Q-Y143R-N155H, and T97A-N155H. Thus, despite a 40% difference in integrase genes between HIV-1 and HIV-2, the genetic pathways leading to raltegravir resistance are similar.